Flight of the Bee: Opera Theater, Ouro Preto, 1824 - Andrea Adour; Cesar Buscacio (Ибероамериканские тетради, 2024)
After 1824, the state of Minas Gerais, with Ouro Preto as its capital, underwent important changes: two years passed since Brazil gained independence, the war ended, the first Constitution was adopted, and the Brazilian periodical press was created. The main newspapers published in Ouro Preto in the early 19th century were chosen as the material to be analyzed in this article, including the «Itacolomi Bee» («Abelha do Itaculumy». Itacolomi means «stone boy» in the Tupi language). The name of the newspaper was typical for the era. Newspaper reviews focused on the Opera House in Ouro Preto, which is considered the oldest in Latin America. The city’s history, public sentiment and events can be traced through the lens of the theatre and through the eyes of travelers.The theater, opened in 1770, staged operas, oratorios and theater plays. The first opera was «St. Bernard» («São Bernardo», 1770) by the Brazilian lawyer, poet and musician Cláudio Manuel da Costa (1729–1789). The opera house, small and modest on the outside, built during the «rich» years of gold mining in Ouro Preto, strikes visitors with baroque opulence inside. This theater is another testament to the city’s development as a special stage of Brazil’s history, and to the preservation of its national heritage today.